2020
DOI: 10.1016/j.eats.2020.05.003
|View full text |Cite
|
Sign up to set email alerts
|

An Arthroscopic Procedure for Restoration of Posterolateral Tibial Plateau Slope in Tibial Plateau Fracture Associated With Anterior Cruciate Ligament Injuries

Abstract: High-energy anterior cruciate ligament (high-energy ACL) injury, occurring in high-energy rotatory trauma of the knee, can accompany a unique fracture pattern that involves depression of the slope of the posterolateral tibial plateau (PLTP). These injuries are challenging to manage due to the lack of a gold-standard arthroscopic procedure that addresses both ACL deficiency and depressed PLTP slope. In such injuries, a one-stage approach may be used to (1) reconstruct the ACL or (2) reduce and fix the avulsed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The correct algorithm for treating these cases is, therefore, still unclear. This study’s relevance, however, lies in that high-grade TPIF should raise awareness of potentially increased rotational instability after ACL reconstruction and, therefore, trigger concurrent ALC reconstruction or TPIF fracture fixation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The correct algorithm for treating these cases is, therefore, still unclear. This study’s relevance, however, lies in that high-grade TPIF should raise awareness of potentially increased rotational instability after ACL reconstruction and, therefore, trigger concurrent ALC reconstruction or TPIF fracture fixation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 25 However, some case reports have illustrated the technical feasibility of simultaneous surgical management of PTPF and ACL tear. 12 , 21 , 35 Menzdorf et al 17 reported that surgical treatment of PTPF combined with ACL repair or reconstruction is a safe procedure and reported good short-term clinical outcomes in a limited sample of patients. Moreover, specific types of PTPF combined with ACL tear have been noted to affect not only pivot-shift laxity under anesthesia but also the postoperative outcomes of ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Park et al. 9 described an arthroscopic treatment of concomitant ACL injury and depressed posterolateral tibial plateau fracture. The reduced fracture is then fixed in situ using a press-fit fibular allograft to stabilize the depressed fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Several surgical techniques have been reported to fix the depressed lateral tibial plateau fractures, including open, fluoroscopic-assisted, and arthroscopic-assisted techniques. 1 , 5 , 6 , 7 , 8 , 9 We propose an arthroscopic-assisted reduction of depressed lateral tibial plateau fractures using an ACL tibial drill guide and a fresh-frozen femoral head allograft.…”
mentioning
confidence: 99%